RF CMOS Oscillators for Modern Wireless Applications. - Babaie, Masoud; Shahmohammadi, Mina.; Staszewski, Robert Bogdan (Milton : River Publishers, 2019)
The main goal of this book is to bring forth the exciting and innovative RF oscillator structures that demonstrate better phase noise performance, lower cost, and higher power efficiency than currently achievable.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books